(untitled) (REMUNOM, 2024)
The red jambo (Syzygium malaccense) is an exotic fruit and ornamental tree that is widely cultivated in the North and Northeast regions of Brazil. Its fruit, the jambo, is very rich in various nutrients, but there is a short period for consumption after harvesting. This work aimed to prepare a sweet red jambo in syrup as a way of extending the time available for consumption of the fruit, and to sensorially analyze the product produced. The results show that the sweet produced has high acceptance, which is indistinct between men and women.